Pengaruh Brand Image dan Brand Ambassador Terhadap Purchase Decision melalui Brand Trust sebagai Intervening - Hera Hera; Finnah Fourqoniah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine whether there is an influence of brand image and brand ambassador on purchase decision through brand trust as an intervening agent for MS Glow consumers in Samarinda City. This study used a quantitative method by collecting data by distributing questionnaires to respondents. The research was conducted on 100 female respondents in the age range of 17-41 years who live in Samarinda City and have purchased MS Glow Beauty Skincare. The sampling technique used in this study was non-probability sampling with purposive sampling method an online. The data that has been collected is then processed using the SmartPLS 3.2.9 analysis tool with the Structural Equation Modeling (SEM)-PLS method. The results of the study show that there is a positive and significant influence on brand image and brand ambassadors on brand trust. However, brand image and brand ambassador have a negative and insignificant effect on purchase decision. Based on the results of the specific indirect effect, brand trust managed to mediate in a positive and significant way the influence of brand image and brand ambassador on purchase decision.